Ligand‐Promoted [Pd]‐Catalyzed α‐Alkylation of Ketones through a Borrowing‐Hydrogen Approach. Issue 1 (2nd January 2023) - Manojveer, Seetharaman; Garg, Nitish K.; Gul, Zarif; Kanwal, Ayesha; Goriya, Yogesh; Johnson, Magnus T.
Abstract: A new class of palladium complexes bearing bidentate 2‐hydroxypyridine based ligands have been prepared and fully characterized. The applications of these new complexes towards ketone alkylation reactions with alcohols through a metal‐ligand cooperative borrowing‐hydrogen (BH) process were demonstrated. Abstract : A new class of palladium complexes bearing 2‐hydroxypyridine‐based ligands has been prepared and fully characterized. The palladium complex 1‐[Pd] (top) has been shown to be an active catalyst for the direct α‐alkylation of ketones with alcohols through the borrowing‐hydrogen approach. The involvement of a metal‐ligand cooperativity pathway was supported by comparison between complexes 1‐[Pd] and 4‐[Pd] (bottom), where the absence of the hydroxyl moiety in 4‐[Pd] led to a decreased activity.